'If You Want Me to Stay, Pay': A Model of Asymmetric Federalism in Centralised Countries. (April 2015) - Claeys, Peter; Martire, Federico
Highly centralised countries like Italy and Spain have devolved fiscal power to regions in an asymmetric way. Some well-off regions get transfers that turn them into net recipients of the fiscal system. We demonstrate in a political economy model of fiscal federalism that, in centralised countries, side-payments are used to compensate regions that are set back by the fiscal system and can credibly threaten to secede. Compensation blocks political negotiation on alternative—more efficient—fiscal systems. We study two regions, Valle d'Aosta in Italy and País Vasco in Spain, as an example.